The Forgotten Complication of Recurrent Nephrolithiasis: “Squamous Cell Carcinoma of the Renal Pelvis”—A Case and Review of the Literature - Tarek Assi; Elie El Rassy; Samah Naderi; Tania Moussa; Maroun Moukarzel; Joseph Kattan (Case Reports in Urology)
Squamous cell carcinoma (SCC) of the renal pelvis is an aggressive tumor with insidious onset of unspecific symptoms and advanced stages at diagnosis. It is a rare entity, accounting for 0.5–8% of renal tumors. In this paper, we describe the case of a patient with a history of recurrent nephrolithiasis that presented with an aggressive form of SCC of the renal pelvis with rapid relapse after resection.